Dorzagliatin monotherapy in Chinese patients with type 2 diabetes: a dose-ranging, randomised, double-blind, placebo-controlled, phase 2 study. Issue 8 (August 2018) - Zhu, Dalong; Gan, Shenglian; Liu, Yu; Ma, Jianhua; Dong, Xiaolin; Song, Weihong; Zeng, Jiao'e; Wang, Guixia; Zhao, Wenjuan; Zhang, Qiu; Li, Yukun; Fang, Hui; et al.
Summary: Background: Glucokinase acts as a glucose sensor in the pancreas and a glucose processor in the liver, and has a central role in glucose homoeostasis. Dorzagliatin is a new, dual-acting, allosteric glucokinase activator that targets both pancreatic and hepatic glucokinases. Dorzagliatin has good pharmacokinetic and pharmacodynamic properties in humans, and provides effective 24-h glycaemic control and improves glucose sensitivity in patients with type 2 diabetes. We aimed to assess the efficacy and safety of dorzagliatin monotherapy at different doses in Chinese patients with type 2 diabetes. Methods: In this multicentre, randomised, double-blind, placebo-controlled, phase 2 study, we randomly assigned (1:1:1:1:1) patients to receive oral placebo or one of four doses of oral dorzagliatin (75 mg once a day, 100 mg once a day, 50 mg twice a day, or 75 mg twice a day) using permuted-block randomisation, with a block size of ten and without stratification. Eligible patients were men or non-fertile women (aged 40–75 years) with type 2 diabetes who had a BMI of 19·0–30·0 kg/m 2, were on a diet and exercise regimen, and were previously untreated or treated with metformin or α-glucosidase inhibitor monotherapy. The study started with a 4-week placebo run-in period followed by a 12-week treatment period. The primary endpoint was the change in HbA1c from baseline to week 12, which was assessed in all patients who received at least one dose of study drug and had both baseline and at least one post-baseline HbA1c value. Safety was assessed in all patients who received at least one dose of study drug. This study is registered withClinicalTrials.gov, numberNCT02561338 . Findings: Between Sept 29, 2015, and Aug 17, 2016, we randomly assigned 258 patients to one of the five study groups. At the end of 12 weeks, the least squares mean change in HbA1c from baseline was −0·35% (95% CI −0·60 to −0·10) in the placebo group, −0·39% (−0·64 to −0·14) in the 75 mg once daily group, −0·65% (−0·92 to −0·38) in the 100 mg once daily group, −0·79% (−1·06 to −0·52) in the 50 mg twice daily group, and −1·12% (−1·39 to −0·86) in the 75 mg twice daily group. Compared with the placebo group, the change in HbA1c between baseline and 12 weeks was significant in the 50 mg twice daily (p=0·0104) and the 75 mg twice daily (p<0·0001) groups. The number of adverse events was similar between the treatment groups and the placebo group. There were no reports of drug-related serious adverse events or severe hypoglycaemia. Interpretation: Dorzagliatin had a beneficial effect on glycaemic control and was safe and well tolerated over 12 weeks in Chinese patients with type 2 diabetes. Funding: Hua Medicine, National Major Scientific and Technological Special Project for Significant New Drugs Development, Shanghai Science and Technology Innovation Action Project, Shanghai Pudong District Science and Technology Innovation Action Project, and Shanghai Municipal Commission of Economy and Informatisation Innovation Action Project.